INTRA‐REGIONAL WAGE INEQUALITY IN PORTUGAL - Pereira, João (2014)
Studies on intra‐regional inequality are scarce, particularly for European countries. This paper aims at further investigating inequality by focusing on wage differences within regions. We consider the case of Portugal, which is considered one of the countries with the highest economic inequality. In particular, we analyse the evolution of intra‐regional wage inequality between 1995 and 2005, employing the quantile based decomposition suggested by Melly (2005), which allows us to study inequality along the entire wage distribution. Our results show that wage inequality evolution has been different for the several regions, as it increased in some regions and decreased in others. Different changes in the work force composition explain these diverse developments.